MODERN CONCEPT OF е-GOVERNANCE AS TOOL FOR PUBLIC ADMINISTRATION MODERNIZATION - Zabeivorota T.V. (Pressing Problems of Public Administration, 2017)
Тhe conceptual analysis of the modernization of public administration is considered in orderto increase its effectiveness. We study the modern concept of governance, which can serve asa benchmark of state-legal reforms and determine the nature of the modernization of publicadministration.